Hamstring muscles` function deficit during overground sprinting in track and field athletes with a history of strain injury - Higashihara, A.; Ono, T.; Tokutake, G.; Kuramochi, R.; Kunita, Y.; Nagano, Y.; Hirose, N. (Journal of Sports Sciences, 2019)
In this study, we aimed to clarify the characteristics of neuromuscular function, kinetics, and kinematics of the lower extremity during sprinting in track and field athletes with a history of strain injury. Ten male college sprinters with a history of unilateral hamstring injury performed maximum effort sprint on an athletic track. The electromyographic (EMG) activity of the long head of the biceps femoris (BFlh) and gluteus maximus (Gmax) muscles and three-dimensional kinematic data were recorded. Bilateral comparisons were performed for the EMG activities, pelvic anterior tilt angle, hip and knee joint angles and torques, and the musculotendon length of BFlh. The activity of BFlh in the previously injured limb was significantly lower than that in the uninjured limb during the late-swing phase of sprinting (p < 0.05). However, the EMG activity of Gmax was not significantly different between the previously injured and uninjured limbs. Furthermore, during the late-swing phase, a significantly more flexed knee angle (p < 0.05) and a decrease in BFlh muscle length (p < 0.05) were noted in the injured limb. It was concluded that previously injured hamstring muscles demonstrate functional deficits during the late swing phase of sprinting in comparison with the uninjured contralateral muscles.